2014
DOI: 10.1002/bjs.9639
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after surgery in patients with previous stroke

Abstract: Patients with previous stroke had a higher risk of adverse postoperative outcomes; their 30-day in-hospital mortality rate was nearly twice that of patients without previous stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…Information available for this study included gender, birth date, disease codes, health care rendered, medicines prescribed, diagnoses at admission and discharge, and medical institutions and physicians providing services. This study employed the All Stroke Database, which consisted of all prevalent and incident stroke patients across Taiwan between 2000 and 2008 [1719]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Information available for this study included gender, birth date, disease codes, health care rendered, medicines prescribed, diagnoses at admission and discharge, and medical institutions and physicians providing services. This study employed the All Stroke Database, which consisted of all prevalent and incident stroke patients across Taiwan between 2000 and 2008 [1719]. …”
Section: Methodsmentioning
confidence: 99%
“…To protect personal privacy, the electronic database was decoded with patient identifications scrambled for further public access for research. Although the National Health Research Institute regulations do not require informed consent due to the use of decoded and scrambled patient identification, this study was approved by Taiwan’s National Health Research Institute (NHIRD-100-122) and the Institutional Review Board of E-DA Hospital, Kaohsiung, Taiwan (2014012) [1719]. …”
Section: Methodsmentioning
confidence: 99%
“…To avoid bias when investigating postoperative adverse outcomes in patients with PD, we used multivariate regression models to adjust these sociodemographic characteristics as potential confounding factors. Previous studies from our database have revealed that diabetes, 12 stroke, 13 heart failure, 22 atrial fibrillation, 23 liver cirrhosis, 14 renal dialysis, 24 chronic obstructive pulmonary disease, 25 and mental disorders 15 were noted as risk factors of perioperative complications and mortality. Some of these coexisting medical conditions were also considered as comorbidities for patients with PD.…”
Section: Discussionmentioning
confidence: 82%
“…Second, severity and disability levels of PD could not be obtained in the administrative data for stratification of perioperative risks. Third, even though the accuracy of major diagnosis codes from the NHIRD has been accepted by peer reviewers of scientific journals, 12,13,1518 the validity of PD, comorbidity, and complication codes employed in this study might still be a concern. To reduce the possibility of misdiagnosis or miscoding, we used the inclusion criteria of at least 3 visits for medical care with physician's primary diagnosis of PD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation